Koelreuteria paniculata leaf-shaped nickel selenide / vanadium selenide self-supporting composite electrode as well as preparation method and application thereof

Ni3Se2/V5Se8 nanosheets were prepared by hydrothermal method and pyrolysis method, forming a leaf-like structure and porous array of leucoderma, solving the problem of insufficient adsorption and desorption capabilities of pure nickel selenide, significantly improving electrocatalytic activity and achieving excellent catalytic performance under different conditions.

CN119615249AActive Publication Date: 2025-03-14XI'AN PETROLEUM UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411774064.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-14
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

The adsorption and desorption capacity of pure nickel selenide in hydrogen protons and oxygen-containing species is insufficient, resulting in its unsatisfactory catalytic performance.

Method used

Ni3Se2/V5Se8 nanosheets were prepared by combining hydrothermal method and pyrolysis method to form a leaf-like structure and porous array to improve the electrocatalytic activity of nickel selenide.

Benefits of technology

It significantly improves the electrocatalytic activity of nickel selenide, can exhibit excellent catalytic properties under alkaline and neutral conditions, is suitable for large-scale production and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005170968730000011
    Figure HDA0005170968730000011
  • Figure HDA0005170968730000012
    Figure HDA0005170968730000012
  • Figure HDA0005170968730000021
    Figure HDA0005170968730000021
Patent Text Reader

Abstract

The invention discloses a koelreuteria paniculata leaf-shaped nickel selenide / vanadium selenide self-supporting composite electrode and a preparation method and application thereof.The preparation method comprises the steps that selenium powder serves as a selenium source, lauryl sodium sulfate and polyvinylpyrrolidone serve as morphology regulating agents, and a vanadium source and an alkali source are mixed to be uniform; a nickel-vanadium-based hydroxide precursor is synthesized on foamed nickel in situ by adopting a hydrothermal reaction method, then selenium powder is added into the precursor, and the integrated Ni3Se2 / V5Se8 / NF self-supporting composite electrode is prepared by adopting a pyrolysis method. On one hand, the oxidation-reduction process in the electrochemical reaction process is accelerated, and the adsorption energy barrier of a reaction intermediate is reduced, so that the catalytic performance of the material is improved; on the other hand, electron transfer in the electro-catalytic reaction process is improved, the catalytic activity is promoted to be improved, it is effectively guaranteed that strong interaction can be formed between the active material and the NF substrate, and the NF substrate shows good mechanical stability and deformation resistance in electrochemical application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electrocatalytic materials and relates to a Koelreuteria leaf-shaped nickel selenide / vanadium selenide self-supporting composite electrode and a preparation method and application thereof. Background Art

[0002] With the intensification of the global energy crisis and the worsening of environmental pollution, the demand for the development of environmentally friendly energy is increasing day by day. Under the long-term resource endowment characteristics of "rich in coal, poor in oil, and little gas" in my country, an energy consumption structure dominated by fossil energy has been formed, which has brought about serious ecological and environmental problems. Against this background, achieving the goals of "carbon peak" and "carbon neutrality" has become the direction of global joint efforts.

[0003] As a renewable energy source with a wide range of sources, flexible and efficient, clean and low carbon, hydrogen energy is regarded as an ideal choice to replace carbon-based fuels. The electrolysis of water to produce hydrogen technology stands out among many hydrogen production methods. This is because the electricity it uses can be supplied by renewable energy (such as solar energy, wind energy, tidal energy, etc.), the raw materials for the reaction are abundant and easy to obtain, and the products are hydrogen and oxygen, which will not pollute the environment (Li, Z.; Sun, L.; Zhang, Y.; Han, Y.; Zhuang, W.; Tian, ​​L.; Tan, W. Coupled and decoupled electrochemical water splitting for boosting hydrogen evolution: A review and perspective, Coordination Chemistry Reviews, 2024, 510: 215837.). Therefore, electrocatalytic water hydrogen production is a promising sustainable method for preparing green hydrogen. At present, precious metal Pt-based materials and Ru / Ir-based materials with high activity are the most widely used electrocatalysts for hydrogen evolution reaction (HER) and oxygen evolution reaction (OER), respectively, but their high cost and scarce reserves severely restrict their development and large-scale application. Therefore, it is crucial to develop low-cost, highly active and highly stable high current density electrocatalysts.

[0004] In recent years, researchers have developed a series of non-precious metal-based catalysts, such as phosphides, sulfides, selenides, carbides and oxides. Among them, transition metal selenides are considered to be a potential bifunctional electrocatalytic material due to their abundant reserves, metal-like properties and adjustable electronic structure (Fan, H.; Jiao, D.; Fan, J.; Wang, D.; Zaman, B.; Zhang, W.; Zhang, L.; Zheng, W.; Cui, X. Kinetically and thermodynamically exposing elementary steps via high-valence Cr-incorporated of nickelselenide for water electrolysis. Nano Research, 2024, 17 (3): 1199-1208.). It is worth noting that nickel selenide exhibits unique physical and chemical properties in the field of photoelectrocatalysis, and has therefore attracted widespread attention. However, problems such as less exposure of nickel selenide active sites and poor intrinsic activity have greatly limited the improvement of catalytic performance. In addition, the adsorption and desorption capacity of pure nickel selenide for hydrogen protons and oxygen-containing species is insufficient, resulting in less than ideal activity (Zhai, L.; Lo, T.; Xu, Z.; Potter, J.; Mo, J.; Guo, X.; Tang, C.; Tsang, S.; Lau, S. In situ phase transformation on nickel-based selenides for enhanced hydrogen evolution reaction in alkaline medium, ACS Energy Letters, 2020, 5(8): 2483-2491.). Therefore, the regulation of the surface and interface structure and electronic structure of nickel selenide is an important strategy to improve the electrocatalytic performance. Summary of the invention

[0005] The purpose of the present invention is to provide a Koelreuteria leaf-shaped nickel selenide / vanadium selenide self-supporting composite electrode and its preparation method and application. The generated Ni3Se2 / V5Se8 nanosheets present a Koelreuteria leaf layered structure and form a porous array, which improves the electrocatalytic activity of the nickel selenide material and solves the problem of insufficient adsorption and desorption capacity of pure nickel selenide for hydrogen protons and oxygen-containing species.

[0006] In order to achieve the above object, the preparation method of the present invention comprises the following steps:

[0007] S1. Mix 6.17-17.21 mg of sodium dodecyl sulfate and 5.42-15.67 mg of polyvinyl pyrrolidone, add 14-16 mL of ultrapure water, and stir to obtain solution A.

[0008] S2. Mix 94.4-102.3 mg of vanadium source and 86-96 mg of alkali source evenly, add 14-16 mL of ultrapure water, stir evenly to obtain solution B, mix solution A and solution B thoroughly, and stir to obtain solution C;

[0009] S3, placing the pretreated nickel foam into solution C, and reacting in a hydrothermal reactor at 120-130° C. for 18-20 hours;

[0010] S4, after the hydrothermal reaction is completed, the mixture is naturally cooled to room temperature, the nickel foam after the reaction is taken out, washed and dried to obtain a nickel-vanadium-based hydroxide precursor;

[0011] S5, putting the precursor obtained in step S4 and 197-221.1 mg of selenium powder into a magnetic boat, placing the magnetic boat in a tube furnace, evacuating the tube furnace, heating to 430-470° C. at a rate of 5-10° C. / min for sintering reaction, and keeping the temperature for 1.8-2.2 h;

[0012] S6. After the heat treatment reaction is completed, a protective gas is introduced and the temperature is cooled to room temperature. The porcelain boat is taken out of the tube furnace and the sample is taken out from the porcelain boat to obtain an integrated nickel selenide / vanadium selenide self-supporting composite electrode Ni3Se2 / V5Se8 / NF.

[0013] The stirring in step S1 is carried out by magnetic stirring and the stirring is uniform at 20-25°C.

[0014] In step S2, the vanadium source is one or more of vanadium chloride, sodium metavanadate, ammonium metavanadate or vanadium acetylacetonate, the alkali source is one or more of urea, sodium hydroxide or potassium hydroxide, and the stirring is performed by magnetic stirring at 20-25° C.

[0015] The nickel foam pretreated in step S3 is prepared by ultrasonically cleaning the cut nickel foam in an acetone solution for 12 to 17 minutes, then pouring it into 2 to 3 mol / L hydrochloric acid for ultrasonic cleaning for 6 to 11 minutes, then washing it alternately with anhydrous ethanol and ultrapure water for 3 to 4 times, and finally vacuum drying it at 20 to 30°C.

[0016] The hydrothermal reaction in step S3 is carried out in a hydrothermal reactor of polytetrafluoroethylene with a filling ratio of 55-65%.

[0017] The washing in step S4 is performed by alternately rinsing with ultrapure water and anhydrous ethanol for 4 to 5 times; and drying at 65 to 75°C.

[0018] The step S5 is to evacuate the tube of the tube furnace: first evacuate the tube and then fill it with hydrogen and argon mixed gas, repeating this process three times, exhausting all the air in the tube and then evacuating the tube into a vacuum environment.

[0019] The protective gas in step S6 is a hydrogen-argon mixed gas of 5% H2 and 95% Ar.

[0020] A nickel selenide / vanadium selenide self-supporting composite electrode having a Koelreuteria leaf shape is prepared according to the above preparation method.

[0021] The prepared nickel selenide / vanadium selenide self-supporting composite electrode with a Koelreuteria leaf shape is used in the electrocatalytic hydrogen evolution and oxygen evolution reactions under alkaline and neutral conditions.

[0022] Compared with the prior art, the present invention has the following specific beneficial effects:

[0023] 1) The present invention adopts a strategy combining hydrothermal method and pyrolysis method to prepare an integrated Ni3Se2 / V5Se8 / NF self-supporting composite electrode. First, a nickel-vanadium-based hydroxide precursor is synthesized in situ by a hydrothermal method. The method has the advantages of simple operation, extremely low cost, easy control of particle size, good dispersibility and high product purity. The synthesized nickel-vanadium-based hydroxide precursor has the advantages of unique layered structure, high specific surface area, unique electronic structure, etc.; then, a pyrolysis method is used to realize the transformation of nickel-vanadium-based hydroxide to Ni3Se2 / V5Se8 / NF phase, which can control the particle size of the product to be lower, the purity to be higher and the uniformity of the morphology, so that the product is suitable for large-scale production, reduces production costs and improves production efficiency.

[0024] 2) The preparation method of the present invention uses two surfactants, sodium dodecyl sulfate (SDS) and polyvinyl pyrrolidone (PVP). The synergistic effect of SDS and PVP can not only prevent the nanoparticles from aggregating with each other to stabilize the reaction system, but also promote full contact between the material and the electrolyte, exposing more electrocatalytic active sites, thereby improving the apparent electrocatalytic activity of the material.

[0025] 3) In the present invention, the nickel foam (NF) not only provides a nickel source, but also the three-dimensional porous structure of the nickel foam ensures that more active sites are exposed to the reaction medium, which is beneficial to increase the effective loading amount of the catalyst and improve the diffusion rate of the reactants. At the same time, the integrated catalytic electrode synthesized in situ exhibits good mechanical stability and deformation resistance in electrochemical applications. As a metal substrate, the nickel foam has good conductivity, which ensures an efficient electron transmission path, thereby improving the kinetics of the electrocatalyst in the electrochemical reaction.

[0026] 4) The present invention constructs a Ni3Se2 / V5Se8 heterostructure electrocatalyst on a NF substrate to improve the electrocatalytic performance of the material. The V element in vanadium selenide can adjust the electron density of the Ni site of nickel selenide, and regulate the adsorption and desorption capacity of the site for hydrogen protons and oxygen-containing species; at the same time, it can improve the oxidation state of the Ni site, accelerate the redox process in the electrochemical reaction, and reduce the adsorption energy barrier of the reaction intermediates, thereby improving the intrinsic electrocatalytic activity of the material.

[0027] 5) When the material of the present invention is used as an electrocatalyst, it can exhibit excellent catalytic performance under alkaline and neutral conditions. Under alkaline conditions, when the current density reaches 100 mA / cm 2 The required HER and OER overpotentials are 168 mV and 280 mV, respectively. Under neutral conditions, when the current density reaches 100 mA / cm 2 The required HER and OER overpotentials are 252 mV and 390 mV, respectively, and the integrated Ni3Se2 / V5Se8 / NF self-supporting composite electrode has good high current density catalytic performance under both alkaline and neutral conditions.

[0028] In summary, the preparation process of the present invention is simple, the production cost is low, the preparation cycle is short, the process is easy to control, the composition and structure are easy to regulate, and the prepared composite material has a sheet array structure, has a faster electron transfer rate, good catalytic activity, strong stability, and high hydrogen production efficiency; the nickel selenide / vanadium selenide (Ni3Se2 / V5Se8 / NF) self-supporting composite electrode prepared on a nickel foam substrate is applied in the field of electrocatalysis, and has excellent high current density electrocatalytic HER and OER performance under alkaline and neutral conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is the X-ray diffraction (XRD) spectrum of the Ni3Se2 / V5Se8 / NF electrocatalytic electrode prepared in Example 1 of the present invention.

[0030] Figure 2 This is a low-magnification scanning electron microscope (SEM) photograph of the Ni3Se2 / V5Se8 / NF electrocatalytic electrode prepared in Example 1 of the present invention.

[0031] Figure 3 This is a high-magnification scanning electron microscope (SEM) photograph of the Ni3Se2 / V5Se8 / NF electrocatalytic electrode prepared in Example 1 of the present invention.

[0032] Figure 4 This is a hydrogen production performance diagram (HER) of the linear sweep voltammetry (LSV) curve of the Ni3Se2 / V5Se8 / NF electrocatalytic electrode prepared in Example 1 of the present invention under alkaline conditions.

[0033] Figure 5 It is an oxygen production performance diagram (OER) of the linear sweep voltammetry (LSV) curve of the Ni3Se2 / V5Se8 / NF electrocatalytic electrode prepared in Example 1 of the present invention under alkaline conditions.

[0034] Figure 6 It is a hydrogen production performance diagram (HER) of the linear sweep voltammetry (LSV) curve of the Ni3Se2 / V5Se8 / NF electrocatalytic electrode prepared in Example 1 of the present invention under neutral conditions.

[0035] Figure 7 It is an oxygen production performance diagram (OER) of the linear sweep voltammetry (LSV) curve of the Ni3Se2 / V5Se8 / NF electrocatalytic electrode prepared in Example 1 of the present invention under neutral conditions. DETAILED DESCRIPTION

[0036] The present invention is further described in detail below with reference to specific embodiments, but is not intended to limit the present invention.

[0037] Embodiment 1:

[0038] 1) Pretreatment of nickel foam: first, the nickel foam cut into pieces of 5 cm × 1 cm × 0.15 cm was ultrasonically cleaned in an acetone solution for 12 min, then poured into a prepared 2 mol / L hydrochloric acid solution for ultrasonic cleaning for 11 min, then rinsed alternately with anhydrous ethanol and ultrapure water for 3 times, and finally vacuum dried at 24° C. for 12 h before use;

[0039] 2) 6.17 mg of sodium dodecyl sulfate and 5.42 mg of polyvinyl pyrrolidone were mixed evenly, and 14 mL of ultrapure water was added. The mixture was stirred with magnetic stirring at 20° C. for 40 min and stirred evenly to obtain solution A;

[0040] 3) 94.4 mg of vanadium chloride and 86 mg of urea were mixed evenly, 14 mL of ultrapure water was added, and the mixture was stirred evenly to obtain solution B. Finally, solution A and mixture B were fully mixed and stirred to obtain solution C; preferably, the stirring was performed by magnetic stirring, and the stirring time was 40 min at 20° C.;

[0041] 4) placing the pretreated nickel foam into solution C and performing a hydrothermal reaction in a polytetrafluoroethylene hydrothermal reactor at a temperature of 120° C. for 20 h; the solution C reacts in the polytetrafluoroethylene hydrothermal reactor at a filling ratio of 56%;

[0042] 5) After the hydrothermal reaction is completed, the product nickel foam is taken out after natural cooling to room temperature, and washed and dried to obtain a nickel-vanadium-based hydroxide precursor; the washing process is washed alternately with ultrapure water and anhydrous ethanol for 4 times; the drying temperature is 65° C. and the time is 6 hours;

[0043] 6) The precursor obtained in step 5) and 197 mg of selenium powder are placed in a magnetic boat, and placed in a tubular furnace, and the inside of the tubular furnace is evacuated to a vacuum environment; the magnetic boat is placed in the tubular furnace, and first evacuated, and then filled with a hydrogen-argon mixed protective gas, and this is repeated three times to exhaust the air in the tube, and then the tube is evacuated to a vacuum environment, and then a sintering reaction is carried out in the tubular furnace, and the temperature is increased at a rate of 5°C / min, the sintering reaction temperature is 430°C, and the insulation time is 2.2h;

[0044] 7) After the heat treatment reaction is completed, a hydrogen-argon mixed gas is introduced for protection, the mixing ratio is 5% H2 + 95% Ar, and when the temperature drops to room temperature, the porcelain boat is taken out from the tube furnace; the sample is taken out from the porcelain boat to obtain an integrated Ni3Se2 / V5Se8 / NF self-supporting composite electrode.

[0045] Figure 1 This is the X-ray diffraction (XRD) spectrum of the Ni3Se2 / V5Se8 / NF electrocatalytic electrode prepared in Example 1 of the present invention. It can be seen that there are three phases, among which the Ni peak (PDF#70-1849) comes from the nickel foam (NF) substrate, and the other two are the peaks of Ni3Se2 (PDF#19-0841) and V5Se8 (PDF#18-1455) grown on the NF substrate, which proves that the present invention successfully prepared the Ni3Se2 / V5Se8 composite on the NF substrate.

[0046] Figure 2 This is a low-magnification scanning electron microscope (SEM) photograph of the Ni3Se2 / V5Se8 / NF electrocatalytic electrode prepared in Example 1 of the present invention. It can be seen that the Ni3Se2 / V5Se8 nanosheets cross each other and grow vertically on the NF substrate to form a uniformly distributed nanosheet array morphology.

[0047] Figure 3 This is a high-magnification scanning electron microscope (SEM) photograph of the Ni3Se2 / V5Se8 / NF electrocatalytic electrode prepared in Example 1 of the present invention. It can be seen that the Ni3Se2 / V5Se8 nanosheets present a Koelreuteria leaf-like structure and form a porous array.

[0048] Figure 4 The linear sweep voltammetry (LSV) curve of the Ni3Se2 / V5Se8 / NF electrocatalytic electrode prepared in Example 1 of the present invention under alkaline conditions shows the hydrogen production performance (HER). The Ni3Se2 / V5Se8 / NF electrode shows good electrocatalytic hydrogen production activity with a current density of 100 mA / cm 2 The required overpotential is 168 mV respectively.

[0049] Figure 5The linear sweep voltammetry (LSV) curve of the Ni3Se2 / V5Se8 / NF electrocatalytic electrode prepared in Example 1 of the present invention shows the oxygen production performance (OER) under alkaline conditions. The Ni3Se2 / V5Se8 / NF electrode shows good electrocatalytic oxygen production activity, and the current density reaches 100 mA / cm 2 The required overpotential is 280 mV respectively.

[0050] Figure 6 The linear sweep voltammetry (LSV) curve of the Ni3Se2 / V5Se8 / NF electrocatalytic electrode prepared in Example 1 of the present invention under neutral conditions shows the hydrogen production performance (HER). The Ni3Se2 / V5Se8 / NF electrode shows good electrocatalytic hydrogen production activity with a current density of 100 mA / cm 2 The required overpotential is 252 mV respectively.

[0051] Figure 7 The linear sweep voltammetry (LSV) curve of the Ni3Se2 / V5Se8 / NF electrocatalytic electrode prepared in Example 1 of the present invention shows the oxygen production performance (OER) under neutral conditions. The Ni3Se2 / V5Se8 / NF electrode shows good electrocatalytic oxygen production activity, and the current density reaches 100 mA / cm 2 The required overpotential is 390 mV respectively.

[0052] Embodiment 2:

[0053] 1) Pretreatment of nickel foam: first, the nickel foam cut into pieces of 5 cm × 1 cm × 0.15 cm was ultrasonically cleaned in an acetone solution for 13 min, then poured into a prepared 3 mol / L hydrochloric acid solution for ultrasonic cleaning for 8 min, then rinsed alternately with anhydrous ethanol and ultrapure water for 4 times, and finally vacuum dried at 30° C. for 11 h for use;

[0054] 2) 8.5 mg of sodium dodecyl sulfate and 7.5 mg of polyvinyl pyrrolidone were mixed evenly, 14 mL of ultrapure water was added, and the mixture was stirred evenly to obtain a solution A; preferably, the stirring was performed by magnetic stirring, and the stirring time was 36 min at 21° C.;

[0055] 3) 96 mg of ammonium metavanadate and 88 mg of urea were mixed evenly, 14 mL of ultrapure water was added, and the mixture was stirred evenly to obtain solution B. Finally, solutions A and B were fully mixed and stirred to obtain solution C; preferably, the stirring was performed by magnetic stirring, and the stirring time was 36 min at 21° C.;

[0056] 4) placing the pretreated nickel foam into solution C for hydrothermal reaction at a temperature of 122° C. for 19.6 h; preferably, solution C is reacted in a polytetrafluoroethylene hydrothermal reactor with a filling ratio of 56%;

[0057] 5) After the hydrothermal reaction is completed, the product nickel foam is taken out after natural cooling to room temperature, and washed and dried to obtain a nickel-vanadium-based hydroxide precursor; the washing process is washed alternately with ultrapure water and anhydrous ethanol for 4 times; the drying temperature is 67° C. and the time is 5.8 h;

[0058] 6) The precursor obtained in step 5) and 202 mg of selenium powder are placed in a magnetic boat, and placed in a tubular furnace, and the inside of the tubular furnace is evacuated to a vacuum environment; the magnetic boat is placed in the tubular furnace, and first evacuated, and then filled with protective gas, and this is repeated three times to exhaust the air in the tube, and then the tube is evacuated to a vacuum environment; then a sintering reaction is carried out in the tubular furnace, and the temperature is increased at a rate of 6°C / min, the sintering reaction temperature is 435°C, and the insulation time is 2.1h;

[0059] 7) After the heat treatment reaction is completed, a protective gas is introduced for protection, and when the temperature drops to room temperature, the porcelain boat is taken out from the tube furnace; the protective gas is a hydrogen-argon mixed gas with a mixing ratio of 5% H2+95% Ar. The sample is taken out from the porcelain boat to obtain an integrated Ni3Se2 / V5Se8 / NF self-supporting composite electrode.

[0060] Embodiment 3:

[0061] 1) Pretreatment of nickel foam: first, the nickel foam cut into pieces of 5 cm × 1 cm × 0.15 cm was ultrasonically cleaned in an acetone solution for 14 min, then poured into a prepared 2 mol / L hydrochloric acid solution for ultrasonic cleaning for 10 min, then rinsed alternately with anhydrous ethanol and ultrapure water for 3 times, and finally vacuum dried at 28° C. for 11 h for use;

[0062] 2) 10.5 mg of sodium dodecyl sulfate and 9.2 mg of polyvinyl pyrrolidone were mixed evenly, 15 mL of ultrapure water was added, and the mixture was stirred evenly to obtain a solution A; preferably, the stirring was performed by magnetic stirring, and the stirring time was 32 min at 22° C.;

[0063] 3) 98 mg of sodium metavanadate and 90 mg of potassium hydroxide were mixed evenly, 15 mL of ultrapure water was added, and the mixture was stirred evenly to obtain solution B. Finally, solutions A and B were fully mixed and stirred to obtain solution C; preferably, the stirring was performed by magnetic stirring, and the stirring time was 32 min at 22° C.;

[0064] 4) placing the pretreated nickel foam into solution C for hydrothermal reaction at a temperature of 125° C. for 19.2 h; preferably, solution C is reacted in a polytetrafluoroethylene hydrothermal reactor with a filling ratio of 60%;

[0065] 5) After the hydrothermal reaction is completed, the product nickel foam is taken out after natural cooling to room temperature, and washed and dried to obtain a nickel-vanadium-based hydroxide precursor; the washing process is washed alternately with ultrapure water and anhydrous ethanol for 4 times; the drying temperature is 70° C. and the time is 5.5 h;

[0066] 6) The precursor obtained in step 5) and 207 mg of selenium powder are placed in a magnetic boat, and placed in a tubular furnace, and the inside of the tubular furnace is evacuated to a vacuum environment; the magnetic boat is placed in the tubular furnace, and first evacuated, and then filled with protective gas, and this is repeated three times to exhaust the air in the tube, and then the tube is evacuated to a vacuum environment; then a sintering reaction is carried out in the tubular furnace, and the temperature is increased at a rate of 7°C / min, the sintering reaction temperature is 440°C, and the insulation time is 2.1h;

[0067] 7) After the heat treatment reaction is completed, a protective gas is introduced for protection, and when the temperature drops to room temperature, the porcelain boat is taken out from the tube furnace; the protective gas is a hydrogen-argon mixed gas with a mixing ratio of 5% H2+95% Ar. The sample is taken out from the porcelain boat to obtain an integrated Ni3Se2 / V5Se8 / NF self-supporting composite electrode.

[0068] Embodiment 4:

[0069] 1) Pretreatment of nickel foam: first, the nickel foam cut into pieces of 5 cm × 1 cm × 0.15 cm was ultrasonically cleaned in an acetone solution for 15 min, then poured into a prepared 3 mol / L hydrochloric acid solution for ultrasonic cleaning for 7 min, then rinsed alternately with anhydrous ethanol and ultrapure water for 4 times, and finally vacuum dried at 26° C. for 12 h for use;

[0070] 2) 12.8 mg of sodium dodecyl sulfate and 11.5 mg of polyvinyl pyrrolidone were mixed evenly, 15 mL of ultrapure water was added, and the mixture was stirred evenly to obtain a solution A; preferably, the stirring was performed by magnetic stirring at 23° C. for 30 min;

[0071] 3) 100 mg of vanadium chloride and vanadium acetylacetonate mixed in a mass ratio of 2:1 and 92 mg of urea and potassium hydroxide mixed in a mass ratio of 1:1 were mixed evenly, 15 mL of ultrapure water was added, and the mixture was stirred evenly to obtain solution B. Finally, solutions A and B were fully mixed and stirred to obtain solution C; preferably, the stirring was performed by magnetic stirring, and the stirring time was 30 min at 23°C;

[0072] 4) placing the pretreated nickel foam into solution C for hydrothermal reaction at a temperature of 126° C. for 19 h; preferably, solution C is reacted in a polytetrafluoroethylene hydrothermal reactor with a filling ratio of 60%;

[0073] 5) After the hydrothermal reaction is completed, the product nickel foam is taken out after natural cooling to room temperature, and washed and dried to obtain a nickel-vanadium-based hydroxide precursor; the washing process is rinsed alternately with ultrapure water and anhydrous ethanol for 5 times; the drying temperature is 72° C. and the time is 5 hours;

[0074] 6) The precursor obtained in step 5) and 212 mg of selenium powder are placed in a magnetic boat, and placed in a tubular furnace, and the inside of the tubular furnace is evacuated to a vacuum environment; the magnetic boat is placed in the tubular furnace, and first evacuated, and then filled with protective gas, and this is repeated three times to exhaust the air in the tube, and then the tube is evacuated to a vacuum environment; then a sintering reaction is carried out in the tubular furnace, and the temperature is increased at a rate of 8°C / min, the sintering reaction temperature is 450°C, and the insulation time is 2h;

[0075] 7) After the heat treatment reaction is completed, a protective gas is introduced for protection, and when the temperature drops to room temperature, the porcelain boat is taken out from the tube furnace; the protective gas is a hydrogen-argon mixed gas with a mixing ratio of 5% H2+95% Ar. The sample is taken out from the porcelain boat to obtain an integrated Ni3Se2 / V5Se8 / NF self-supporting composite electrode.

[0076] Embodiment 5:

[0077] 1) Pretreatment of nickel foam: first, the nickel foam cut into a size of 5 cm × 1 cm × 0.15 cm was ultrasonically cleaned in an acetone solution for 16 min, then poured into a prepared 2 mol / L hydrochloric acid solution for ultrasonic cleaning for 9 min, then rinsed alternately with anhydrous ethanol and ultrapure water for 3 times, and finally vacuum dried at 22° C. for 13 h before use;

[0078] 2) 15 mg of sodium dodecyl sulfate and 13.5 mg of polyvinyl pyrrolidone were mixed evenly, and 16 mL of ultrapure water was added, and stirred evenly to obtain solution A; preferably, the stirring was performed by magnetic stirring, and the stirring time was 25 min at 24° C.;

[0079] 3) 101 mg of sodium metavanadate and ammonium metavanadate mixed in a mass ratio of 1:1 and 94 mg of sodium hydroxide and potassium hydroxide mixed in a mass ratio of 1:1 were mixed evenly, poured into 16 mL of ultrapure water, and stirred evenly to obtain solution B. Finally, solutions A and B were fully mixed and stirred to obtain solution C; preferably, the stirring was performed by magnetic stirring, and the stirring time was 25 min at 24°C;

[0080] 4) placing the pretreated nickel foam into solution C for hydrothermal reaction at a temperature of 128° C. for 18.5 h; preferably, solution C is reacted in a polytetrafluoroethylene hydrothermal reactor with a filling ratio of 64%;

[0081] 5) After the hydrothermal reaction is completed, the product nickel foam is taken out after natural cooling to room temperature, and washed and dried to obtain a nickel-vanadium-based hydroxide precursor; the washing process is rinsed alternately with ultrapure water and anhydrous ethanol for 5 times; the drying temperature is 73° C. and the time is 4.5 h;

[0082] 6) The precursor obtained in step 5) and 216 mg of selenium powder are placed in a magnetic boat, and placed in a tubular furnace, and the inside of the tubular furnace is evacuated to a vacuum environment; the magnetic boat is placed in the tubular furnace, and first evacuated, and then filled with protective gas, and this is repeated three times to exhaust the air in the tube, and then the tube is evacuated to a vacuum environment; then a sintering reaction is carried out in the tubular furnace, and the temperature is increased at a rate of 9°C / min, the sintering reaction temperature is 460°C, and the insulation time is 1.9h;

[0083] 7) After the heat treatment reaction is completed, a protective gas is introduced for protection, and when the temperature drops to room temperature, the porcelain boat is taken out from the tube furnace; the protective gas is a hydrogen-argon mixed gas with a mixing ratio of 5% H2+95% Ar; the sample is taken out from the porcelain boat to obtain an integrated Ni3Se2 / V5Se8 / NF self-supporting composite electrode.

[0084] Embodiment 6:

[0085] 1) Pretreatment of nickel foam: first, the nickel foam cut into a size of 5 cm × 1 cm × 0.15 cm was ultrasonically cleaned in an acetone solution for 17 min, then poured into a prepared 3 mol / L hydrochloric acid solution for ultrasonic cleaning for 6 min, then rinsed alternately with anhydrous ethanol and ultrapure water for 4 times, and finally vacuum dried at 20° C. for 13 h before use;

[0086] 2) 17.2 mg of sodium dodecyl sulfate and 15.67 mg of polyvinyl pyrrolidone were mixed evenly, 16 mL of ultrapure water was added, and the mixture was stirred evenly to obtain a solution A; preferably, the stirring was performed by magnetic stirring at 25° C. for 20 min;

[0087] 3) 102.3 mg of vanadium acetylacetonate and 96 mg of sodium hydroxide were mixed evenly, 16 mL of ultrapure water was added, and the mixture was stirred evenly to obtain solution B. Finally, solution A and solution B were fully mixed and stirred to obtain solution C; preferably, the stirring was performed by magnetic stirring, and the stirring time was 20 min at 25° C.;

[0088] 4) placing the pretreated nickel foam into solution C for hydrothermal reaction at a temperature of 130° C. for 18 h; preferably, solution C is reacted in a polytetrafluoroethylene hydrothermal reactor with a filling ratio of 64%.

[0089] 5) After the hydrothermal reaction is completed, the product nickel foam is taken out after natural cooling to room temperature, and washed and dried to obtain a nickel-vanadium-based hydroxide precursor; the washing process uses ultrapure water and anhydrous ethanol to rinse alternately 5 times; the drying temperature is 75° C. and the time is 4 hours.

[0090] 6) The precursor obtained in step 5) and 221.1 mg of selenium powder are placed in a magnetic boat, and placed in a tubular furnace, and the inside of the tubular furnace is evacuated to a vacuum environment; the magnetic boat is placed in the tubular furnace, and first evacuated, and then filled with protective gas, and this is repeated three times to exhaust the air in the tube, and then the tube is evacuated to a vacuum environment; then a sintering reaction is carried out in the tubular furnace, and the temperature is increased at a rate of 10°C / min, the sintering reaction temperature is 470°C, and the insulation time is 1.8h;

[0091] 7) After the heat treatment reaction is completed, a protective gas is introduced for protection, and when the temperature drops to room temperature, the porcelain boat is taken out from the tube furnace; the protective gas is a hydrogen-argon mixed gas with a mixing ratio of 5% H2+95% Ar; the sample is taken out from the porcelain boat to obtain an integrated Ni3Se2 / V5Se8 / NF self-supporting composite electrode.

[0092] The V element in the vanadium selenide of the present invention can regulate the electron density of the Ni site of the nickel selenide, and regulate the adsorption and desorption capacity of the site for hydrogen protons and oxygen-containing species. At the same time, the oxidation state of the Ni site can be improved, the redox process in the electrochemical reaction process can be accelerated, and the adsorption capacity of the reaction intermediates can be reduced, thereby improving the catalytic performance of the material. On the other hand, the in-situ liquid phase growth technology assisted by the structure regulator is not only conducive to the full exposure of the electrochemical active sites of the catalytic material grown on its surface, improving the electron transfer in the electrocatalytic reaction process, and promoting the improvement of the catalytic activity, but also effectively ensures that a strong interaction can be formed between the active material and the NF substrate, so that it exhibits good mechanical stability and deformation resistance in electrochemical applications.

Claims

1. A method for preparing a leaf-shaped nickel selenide / vanadium selenide self-supporting composite electrode, characterized in that: The steps include: S1. Mix 6.17-17.21 mg of sodium dodecyl sulfate and 5.42-15.67 mg of polyvinyl pyrrolidone, add 14-16 mL of ultrapure water, and stir to obtain solution A. S2. Mix 94.4-102.3 mg of vanadium source and 86-96 mg of alkali source evenly, add 14-16 mL of ultrapure water, stir evenly to obtain solution B, mix solution A and solution B thoroughly, and stir to obtain solution C; S3, placing the pretreated nickel foam into solution C, and reacting in a hydrothermal reactor at 120-130° C. for 18-20 hours; S4, after the hydrothermal reaction is completed, the mixture is naturally cooled to room temperature, the nickel foam after the reaction is taken out, and the nickel-vanadium-based hydroxide precursor is obtained after washing and drying; S5, putting the precursor obtained in step S4 and 197-221.1 mg of selenium powder into a magnetic boat, placing the magnetic boat in a tube furnace, evacuating the tube furnace, heating to 430-470° C. at a rate of 5-10° C. / min for sintering reaction, and keeping the temperature for 1.8-2.2 h; S6. After the heat treatment reaction is completed, a protective gas is introduced and the temperature is cooled to room temperature. The porcelain boat is taken out of the tube furnace and the sample is taken out from the porcelain boat to obtain an integrated nickel selenide / vanadium selenide self-supporting composite electrode Ni3Se2 / V5Se8 / NF.

2. The method for preparing a leaf-shaped nickel selenide / vanadium selenide self-supporting composite electrode according to claim 1, characterized in that: The stirring in step S1 is carried out by magnetic stirring and the stirring is uniform at 20-25°C.

3. The method for preparing a leaf-shaped nickel selenide / vanadium selenide self-supporting composite electrode according to claim 1, characterized in that: In step S2, the vanadium source is one or more of vanadium chloride, sodium metavanadate, ammonium metavanadate or vanadium acetylacetonate, the alkali source is one or more of urea, sodium hydroxide or potassium hydroxide, and the stirring is performed by magnetic stirring at 20-25° C.

4. The method for preparing a leaf-shaped nickel selenide / vanadium selenide self-supporting composite electrode according to claim 1, characterized in that: The nickel foam pretreated in step S3 is prepared by ultrasonically cleaning the cut nickel foam in an acetone solution for 12 to 17 minutes, then pouring it into 2 to 3 mol / L hydrochloric acid for ultrasonic cleaning for 6 to 11 minutes, then washing it alternately with anhydrous ethanol and ultrapure water for 3 to 4 times, and finally vacuum drying it at 20 to 30°C.

5. The method for preparing a leaf-shaped nickel selenide / vanadium selenide self-supporting composite electrode according to claim 1, characterized in that: The hydrothermal reaction in step S3 is carried out in a hydrothermal reactor of polytetrafluoroethylene with a filling ratio of 55-65%.

6. The method for preparing a Koelreuteria leaf-shaped nickel selenide / vanadium selenide self-supporting composite electrode according to claim 1, characterized in that: The washing in step S4 is performed by alternately rinsing with ultrapure water and anhydrous ethanol for 4 to 5 times; and drying at 65 to 75°C.

7. The method for preparing a Koelreuteria leaf-shaped nickel selenide / vanadium selenide self-supporting composite electrode according to claim 1, characterized in that: The step S5 is to evacuate the tube of the tube furnace: first evacuate the tube and then fill it with hydrogen and argon mixed gas, repeating this process three times, exhausting all the air in the tube and then evacuating the tube into a vacuum environment.

8. The method for preparing a Koelreuteria leaf-shaped nickel selenide / vanadium selenide self-supporting composite electrode according to claim 1, characterized in that: The protective gas in step S6 is a hydrogen-argon mixed gas of 5% H2 and 95% Ar.

9. A nickel selenide / vanadium selenide self-supporting composite electrode having a Koelreuteria leaf shape prepared by the method according to any one of claims 1 to 8.

10. Use of the nickel selenide / vanadium selenide self-supporting composite electrode having a Koelreuteria leaf shape as claimed in claim 9 in electrocatalytic hydrogen evolution and oxygen evolution reactions under alkaline and neutral conditions.

Citation Information

Patent Citations

  • Preparation method of flaky nickel-vanadium bimetallic hydroxide

    CN107311243A

  • NiV-LDH-NF hydrogen production electrode with optimized electronic structure, and preparation method and application of NiV-LDH-NF hydrogen production electrode

    CN110760879A

  • Vanadium-doped nickel selenide heterojunction self-supporting electrode and preparation method and application thereof

    CN111996543A